Analisis Sistem Irigasi Sawah Tadah Hujan di Kecamatan Tompobulu Kabupaten Bantaeng - Yunita, Yunita; Yusuf, Andi Rumpang; Badrun, Burhanuddin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2024)
Irrigation is an effort to bring in water by making it buildings and channels to paddy fields or fields according to plant needs. Around 86% of national rice production comes from irrigated rice fields. The aim of this research is to determine the irrigation system for rainfed rice fields and sources of rainfall water for irrigation of rainfed rice fields in Tompobulu District, Bantaeng Regency. This research method uses a qualitative descriptive method, with data collection techniques, namely surveys and observations. The results of the analysis show that the Tompobulu District Irrigation Area uses a non-technical irrigation system where the irrigation network is usually managed independently by farmer groups by relying on rainfall in rice fields without permanent buildings. The irrigation area has an irrigation area of 557 ha. The source of irrigation for rainfed rice fields in Tompobulu District comes from rainfall that falls directly on the rice fields to be used as a source of irrigation water in the irrigation areas.